The inquisitor's apprentice - Moriarty, Chris, 1968- (Harcourt Children's Books, 2011)
In early twentieth-century New York, Sacha Kessler's ability to see witches earns him an apprenticeship to the police department's star Inquisitor, Maximillian Wolf, to help stop magical crime and, with fellow apprentice Lily Astral, Sacha investigates who is trying to kill Thomas Edison, whose mechanical witch detector that could unleash the worst witch-hunt in American history.